Oil degradation and biosurfactant production by the deep sea bacterium Dietzia maris As-13-3 - Wang, Wanpeng; Cai, Bobo; Shao, Zongze (Frontiers in Microbiology, 2014)
Abstract: Recent investigations of extreme environments have revealed numerous bioactive natural products. However, biosurfactant-producing strains from deep sea extreme environment are largely unknown. Here, we show that Dietzia maris As-13-3 isolated from deep sea hydrothermal field could produce di-rhamnolipid as biosurfactant. The critical micelle concentration (CMC) of the purified di-rhamnolipid was determined to be 120 mgL-1, and it lowered the surface tension of water from 74±0.2 mN m-1 to 38±0.2 mN m-1. Further, the alkane metabolic pathway-related genes and di-rhamnolipid biosynthesis-related genes were also analyzed by the sequencing genome of D. maris As-13-3 and quantitative real-time PCR (Q-PCR), respectively. Q-PCR analysis showed that all these genes were induced by n-Tetradecane, n-Hexadecane and pristane. To the best of our knowledge, this is first report about the complete pathway of the di-rhamnolipid synthesis process in the genus Dietzia. Thus, our study provided the insights into Dietzia in respects of oil degradation and biosurfactant production, and will help to evaluate the potential of Dietzia in marine oil removal.